Pteridophytes of Eastern India - Panigrahi, G.; Patnaik, S. N. (Indian Forester, 1961)
The necessity for revising Beddome's out of date hand book of ferns of British India, Ceylon and Malaya Peninsula and the urgency for publishing an enumeration of the Indian fern species with correct nomenclature have been stressed. A list of 23 genera and 79 species of Polypodiaceae sensu Copeland (1947), distributed in various parts of India, with correct nomenclature, is appended to serve as a useful guide on nomenclature to Indian taxonomists working on the family. Two species as new records for India and one species as new record for Eastern India have been established.